Pre-Service Teachers' Attitudes Towards the Use of Zoom Meetings for Microteaching Class - Lisa Rakhmanina; Nila Kencana; Melati Melati (English Education Study Program Faculty of Teacher Training and Education, 2022)
Microteaching for pre-service teacher’s instruction has traditionally been face-to-face as these teachers are prepared to teach in secondary schools. However, these pre-service teachers were also aware of the requirement for teaching synchronously via online platforms if face-to-face classes were not possible for example like in time COVID-19. The objective of this study is to investigate pre-service teacher’s or students' perspectives of utilizing the Zoom meeting application for online microteaching classes from pedagogical, socio-cultural, and technical perspectives. This study's population comprised of twenty (20) students from the Faculty of Teacher Training and Education who had enrolled in microteaching lessons and were, of course, permitted to express their thoughts and opinions. It can be stated that students have a favorable opinion of the Zoom meeting application for online microteaching classes. The study's findings indicate a beneficial outcome in the delivery of microteaching lectures online. Even though the courses are delivered online, they follow the usual format. Students appear to prefer the Zoom Meeting application as a learning medium for interactive learning applications because, in addition toward being practical and straightforward, zoom meetings rarely bring difficult-to-manage problems.